Analysis of the Marketing Channels for Mekar Mandiri Fish Crackers in Sidolego Village, Tabir Lintas District, Merangin Regency, Jambi, Indonesia - Asnawati Is Asnawati Is; Putri Indah Kumala Ratih; Isyaturiyadhah Isyaturiyadhah (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
Indonesia, as an agrarian and maritime country, has significant potential to develop fish-based processed products from home industries to create added value and strengthen the local economy. However, limited empirical studies on fish-based processed products (particularly fish crackers) have yielded insufficient information on the marketing channel structure and the distribution of economic benefits to producers. This study aims to analyze the marketing channel patterns and marketing efficiency of Mekar Mandiri Fish Crackers in Sidolego Village, Tabir Lintas District, Merangin Regency, Jambi Province. The research used a descriptive case study design with purposive location selection. Primary data were collected through observation and structured interviews with producers and marketers, using purposive and snowball sampling. The analysis was conducted by mapping the marketing channels and calculating the farmer's share as an indicator of efficiency. The results showed that there were three marketing channels: (i) producer–consumer, (ii) producer–retailer–consumer, and (iii) producer–wholesaler–retailer–consumer. Channels I and II have a farmer's share of 100%, while channel III has an 83.3% share, indicating the allocation of margins to intermediaries. These findings confirm that shorter marketing channels provide higher efficiency and strengthen the bargaining position of producers, while longer channels play a role in expanding distribution reach. This study provides empirical evidence on non-coastal rural microenterprises and serves as a basis for formulating marketing strategies that balance efficiency and market expansion to support the sustainability of fishery-based home industries.